2023
DOI: 10.3390/endocrines4020024
|View full text |Cite
|
Sign up to set email alerts
|

The Promising Role of Self-Compassion in Managing Type 1 Diabetes

Abstract: Given the demanding daily regimen for type 1 diabetes (T1D) and emphasis on personal responsibility for self-management, people with T1D can experience self-criticism and diabetes distress. How an individual responds to and copes with diabetes-related feedback may influence self-care, health outcomes, and overall well-being. Self-compassion in the context of diabetes has limited but promising research on its ability to alleviate distress in people with T1D. This narrative review captures relevant, existing lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 120 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…DM patients are at risk of experiencing stress as much as 2 times (Kaelberer & Tanenbaum, 2023). Studies show that stress can affect blood sugar levels in diabetes mellitus patients, including in elderly diabetes mellitus patients.Stress in diabetic patients is a serious problem because it makes the disease worse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM patients are at risk of experiencing stress as much as 2 times (Kaelberer & Tanenbaum, 2023). Studies show that stress can affect blood sugar levels in diabetes mellitus patients, including in elderly diabetes mellitus patients.Stress in diabetic patients is a serious problem because it makes the disease worse.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that selfcompassion may help improve regimen adherence and decrease HbA1c in individuals with diabetes. In research conducted by (Kaelberer & Tanenbaum, 2023), self-compassion was shown to help reduce stress and improve psychological well-being in individuals with diabetes. This study suggests that self-compassion may help improve psychological wellbeing in individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%